2016
DOI: 10.1016/j.jpsychires.2016.02.005
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced default mode network connectivity with ventral striatum in subthreshold depression individuals

Abstract: Subthreshold depression (StD) is a highly prevalent condition associated with increased service utilization and social morbidity. Nevertheless, due to limitations in current diagnostic systems that set the boundary for major depressive disorder (MDD), very few brain imaging studies on the neurobiology of StD have been carried out, and its underlying neurobiological mechanism remains unclear. In recent years, accumulating evidence suggests that the disruption of the default mode network (DMN), a network involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 66 publications
3
50
0
Order By: Relevance
“…A core characteristic of patients with depression is the loss of interest in pleasurable activities and limitations in multiple dimensions of well-being (Bogdan, Nikolova, & Pizzagalli, 2013; Hasler & Northoff, 2011; Hwang et al, 2016; Naranjo, Tremblay, & Busto, 2001; Russo & Nestler, 2013). The reward system (Bluhm et al, 2009; Naranjo et al, 2001; Pizzagalli et al, 2009) is involved in pleasure and motivation, which have been proven to play important roles in the pathophysiology of MDD (Bluhm et al, 2009; Soares et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A core characteristic of patients with depression is the loss of interest in pleasurable activities and limitations in multiple dimensions of well-being (Bogdan, Nikolova, & Pizzagalli, 2013; Hasler & Northoff, 2011; Hwang et al, 2016; Naranjo, Tremblay, & Busto, 2001; Russo & Nestler, 2013). The reward system (Bluhm et al, 2009; Naranjo et al, 2001; Pizzagalli et al, 2009) is involved in pleasure and motivation, which have been proven to play important roles in the pathophysiology of MDD (Bluhm et al, 2009; Soares et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We found that the resting state functional connectivity between the subgenual ACC and the default mode network was significantly associated with symptom severity in StD patients (Hwang et al, 2016). The abnormal function and structure of the ACC/mPFC has been regarded as a biomarker in MDD (Phillips et al, 2015).…”
Section: Discussionmentioning
confidence: 91%
“…Pizzagalli, 2011, Silbersweig, 2013). Many brain regions including the amygdala, hippocampus, insula, ventral striatum, ventral anterior cingulate gyrus, and prefrontal cortex are involved in the neural pathology and development of MDD (Lawrence et al, 2004, Phillips et al, 2015, Phillips et al, 2003a, Phillips et al, 2003b) and subthreshold depression (Hwang et al, 2016). Among these brain regions, one of the most well-studied regions is the amygdala.…”
Section: Introductionmentioning
confidence: 99%